Role-specific performance profiles of professional cyclists in a Grand Tour - Sánchez-Jiménez, J. L.; Javaloyes, A.; Barranco-Gil, D.; Peña-González, I.; Moya-Ramón, M.; Mateo-March, M. (European Journal of Sport Science, 2026)
ABSTRACT Professional cycling in Grand Tours involves varied stage types and rider roles, but intra-stage workload dynamics remain underexplored. Observational study of 36 male professional cyclists in the 2020 Vuelta a España, categorized as climbers ( n = 13), all-rounders ( n = 13), and flat specialists ( n = 10). Power meter data from 17 stages (3 flat, 9 semi-mountainous, 5 mountain) were analyzed using principal component analysis and mixed models to assess changes across stage progression (0%-100%). Climbers showed high initial high-intensity power in mountain stages, decreasing by 40.70 W per 10%, with average power increasing by 8.45 W per 10%. All-rounders' average power increased by 0.25 W per 10% in mountain, 0.03 W in semi-mountainous, and 10.40 W in flat stages. Flat specialists' average power increased by 0.26 W in mountain, decreased by 0.04 W in semi-mountainous, and increased by 9.29 W in flat stages. Mountain stages had high initial intensity with efficiency rising by 0.02 per 10%; semi-mountainous stages showed mixed patterns; flat stages had power increases of 9.29-10.40 W per 10%. Workload varies by role and stage, offering insights for targeted training and tactics in Grand Tours.